The biggest lie in the history of Christianity - Kelly, Matthew (North Palm Beach, Florida : Eucalyptus Media Group, 2018)
Do you believe it's possible to be happier than you have ever been before? Not for fleeting moments, but consistently? We all want to be happy and live life to the fullest, but the answer isn't found in the world's definition of happiness. Modern culture is constantly feeding us lies, and these lies affect you more than you know. The lies that affect you the most, however, are the ones you tell yourself. These lies steal your joy, sap your energy, and cause you to lose hope. They prevent you from discovering the kind of vibrant faith the first Christians experienced. But as Kelly shows, we've arrived at a crucial moment in history. People are disillusioned with what the world offers. The world is in desperate need of change, and no one is in a better position to effect that change than Christians. We have an incredible opportunity to dispel the lies and cut through the confusion and false promises around us. Together we can change the course of history--with humility, generosity, kindness, and joy, one Holy Moment at a time.
1. Life is a puzzle -- 2. Your happiness project -- 3. The false promises and lies of this world -- 4. I've been lying to myself -- 5. So many lies about Christianity -- 6. The biggest lie -- 7. Prove it! -- 8. One beautiful truth -- 9. The world needs changing -- 10. It's been done before -- 11. History is presenting Christianity with a new opportunity -- 12. Everyday miracles -- 13. Live an intriguing life -- 14. Our dirty little secret -- 15. Now is your time!
Keywords: Happiness -- Religious aspects -- Christianity; Christian life; Christian life; Happiness -- Religious aspects -- Christianity; Nonfiction